P125 Basement membrane remodelling as a biomarker for monitoring disease activity in Crohn's disease patients: the role of laminin. (16th January 2018) - Olesen, M L; Di Sabatino, A; Mazza, G; Manon-Jensen, T; Giuffrida, P; Pinzani, M; Krag, A; Karsdal, M; Kjeldsen, J; Mortensen, J H
Abstract: Background: Patients with inflammatory bowel disease (IBD) have varying disease courses with phases of inactive disease and flares of active disease with impairment of the intestinal epithelial barrier leading to tissue damage. Due to the large surface area, basement membrane is abundant in the intestinal tissue and its constituents, such as laminins, play an important role in the intestinal epithelial homeostasis. The laminin gamma 1 chain is highly abundant along the entire crypt-villus axis in the basement membrane. We investigated if a serum biomarker of the basement membrane (LG1M) could serve as surrogate biomarkers for disease activity in a rat in vivo colitis model and in IBD patients. Methods: Serum from male Sprague Dawley rats that received 5–6% dextran sulfate sodium (DSS) ( n = 21) or regular drinking water ( n = 9) for 5 days was included and scored for disease activity index (DAI). In addition, serum from 44 Crohn's disease (CD) patients with inactive ( n = 20) or active ( n = 24) disease and healthy subjects ( n = 20) was included in this study. A competitive ELISA for matrix metalloproteinase (MMP) 9 mediated degradation of the laminin gamma 1 chain (LG1M) was used to estimate the level of laminin degradation in serum. Sections of the distal colon from the rats were assessed histologically for structural changes. Results: LG1M were significantly elevated in CD patients serum compared with healthy subjects ( p < 0.001; p < 0.001), but with lower levels in active CD compared inactive CD (Figure 1A). The findings of LG1M were confirmed in the in vivo colitis model, in which the levels of LG1M in DSS rat serum with high DAI were significantly lower ( p = 0.004) compared with controls (Figure 1B). LG1M correlated negatively to DAI ( r 2 = 0.2153; p < 0.01) (Figure 1C). The structure of the distal colonic tissue in DSS rats was disrupted compared with controls with loss of crypt architecture and total surface area (Figure 1D–E). Conclusions: Our data indicate that the basement membrane biomarker, LG1M, may be applied as non-invasive surrogate biomarker of disease activity in CD patients and thus aid in monitoring patients. We report lower serum levels of LG1M in active disease compared with inactive disease in both the in vivo model and patient samples. The decreased amount of LG1M during active disease corresponds to the apparent loss of surface area in the intestine, which results in a reduction of the total amount of laminins for MMP-mediated degradation.